Censorship Moments Reading Texts in the History of Censorship and Freedom of Expression - Kemp, Geoff (Textual Moments in the History of Political Thought, 2014)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Censorship in varying forms has been part of human experience for 2,500 years and has proved itself to be a recurring presence for political thought, whether as active repression, a shaping context for expression, or as itself a subject for analysis and argument. From the death of Socrates to the fatwa against Salman Rushdie, attempts to silence thinkers and writers have provoked passionate and often penetrating responses that speak of their historical moment. Censorship Moments will provide short, accessible and stimulating access to a variety of these responses. Each chapter will couple a short textual 'moment' of writing on censorship and freedom of expression by a past writer with analysis by an expert current scholar. The book's main focus is the public political dimension of censorship, in its relation to political authority and political thought, while also reflecting on the porous boundary to literature and other areas such as law and the media.